Assessing Treatment Efficacy: Brief vs. Ultra brief Pulse Widths in Bitemporal Modified Electroconvulsive Therapy - Yadav, Vishesh; Pathak, Abhishek; Singh, Rahul; Singh, Manish; Yogi Rana (Nepal Journal of Neuroscience, 2025)
Introduction Modified electroconvulsive therapy (MECT) is widely utilized for severe psychiatric disorders, with ongoing exploration of stimulus parameters to maximize efficacy. The pulse width in electroconvulsive therapy (ECT), specifically brief pulse (1.5 ms) versus ultra brief pulse (0.5 ms), may significantly influence clinical outcomes. However, comparative data on efficacy in rural Indian settings are limited. Our objective was to compare the clinical efficacy of brief and ultra brief pulse widths in bitemporal modified ECT in patients with severe psychiatric disorders. Methods: This prospective, randomized comparative study was conducted at a rural tertiary care hospital in Northern India. Sixty-six patients aged between 18 and 60 years, diagnosed with schizophrenia, schizoaffective disorder, bipolar disorder, or severe depression, were randomly allocated to receive either brief or ultra brief pulse bitemporal MECT. Clinical efficacy was measured using standardized symptom rating scales including PANSS, BDI, YMRS, and CGI-S, administered pre- and post-treatment. Results: Both brief and ultra brief pulse width groups demonstrated comparable clinical efficacy across schizophrenia, schizoaffective disorder, bipolar disorder, and severe depression, with no statistically significant differences observed in symptom reduction between the two groups (p > 0.05). Conclusion: Brief and ultra brief pulse widths in bitemporal modified ECT exhibited similar clinical efficacy in the treatment of major psychiatric disorders. Given their equivalence in therapeutic outcomes, both pulse widths may be considered viable options for clinicians. Further studies with larger samples and diverse populations are recommended to reinforce these findings.